Transient thermodynamic modeling and economic assessment of cogeneration system based on compressed air energy storage and multi-effect desalination. (25th November 2022) - Assareh, Ehsanolah; Jafari, Majid; Keykhah, Sajjad; Lee, Moonyong
Abstract: This study examined the design of a renewable system for producing electricity and freshwater based on the solar cycle and using thermal storage in different cities. The system comprised heliostat, gas turbine, multi-effect desalination, and compressed air energy storage (CAES) subsystems. The Engineering Equation Solver software was used for modeling and obtaining results by system analysis. Eight scenarios were examined by considering the charging time, discharging time, number of sunny hours, and various desalination effects. Finally, the best scenario was selected following a parametric study, which was scenario 5 with seven parameters, and it had the best performance. Specifically, the exergy round trip efficiency, round trip efficiency, power generation, and freshwater generation rate of the system were optimal. The number of heliostats and the turbine and compressor efficiencies influenced the system outputs. Based on an economic analysis of the system, the CAES, solar unit, and gas turbine costs were the highest among the system component costs. Moreover, based on an exergy analysis of the system, most exergy degradation corresponded to the heliostats, receiver, and gas turbine. Moreover, five cities—Esfahan, Dubai, London, Paris, and San Francisco—were compared in terms of the peak consumption time per year. Finally, the performance of the developed system was investigated for ambient temperature changes, solar radiation, and wind speed of the cities considered per year. The outcomes revealed that the system performed the best in the climate conditions of Esfahan during the peak consumption time. Highlights: A renewable system for producing electricity and freshwater based on the solar cycle through thermal storage The eight scenarios by considering charging time, discharging time, the sunny hours number Comparison among the five cities of Isfahan, Dubai, London, Paris, and San Francisco for peak consumption time per year Best performance is in Isfahan's climate conditions during the peak consumption time.